Evaluation of Laboratory Toxicities and Field Application of Plant Spray Oil and Its Mixture with Metarhizium anisopliae Against Diaphorina citri Kuwayama (Hemiptera: Liviidae) - Dasong Chen; Jiaqi Suo; Jianquan Yan; Lijia Chen; Fenghao Chen; Jianying Huang; Haitao Duan; Gecheng Ouyang; Xiang Meng (Insects)
Overusing chemicals to manage Diaphorina citri has created insecticide resistance and negative impacts on the natural ecosystem. This has prompted the need to develop new methods of control. In the present study, we evaluated the toxicity of plant spray oil, Metarhizium anisopliae, and their combined formulations against D. citri adults through laboratory bioassays. We tested varying concentrations and application doses of the individual agents and their mixtures to determine synergistic effects. The optimal mixing ratio of M. anisopliae and plant spray oil for enhanced pest control efficacy was also identified. The results showed that the control effect of plant spray oil and M. anisopliae on D. citri became more pronounced as the concentration increased. When the two were mixed in different proportions, the synergistic effect of plant spray oil was the strongest when the mixing ratio was 5:5. Field trials demonstrated that a combined treatment of plant spray oil emulsion (9.10 g/L) and M. anisopliae (1 × 108 spores/mL) achieved over 80% relative control efficacy against adult D. citri by the 6th day post-treatment. Its efficacy further increased to 96.28% by the 8th day, demonstrating its potential to replace chemical control methods. This study provides a practical example for exploring biopesticides and leveraging the synergistic effects of biogenic pesticides in preventing and controlling pests.